2005
DOI: 10.1039/b511257e
|View full text |Cite
|
Sign up to set email alerts
|

Water molecule clusters measured at water/air interfaces using atomic force microscopy

Abstract: During the tip approach to hydrophobic surfaces like the water/air interface, the measured interaction force reveals a strong attraction with a range of approximately 250 nm at some points along the interface. The range of this force is approximately 100 times larger than the measured for gold (approximately 3 nm) and 10 times larger than the one for hydrophobic silicon surfaces (approximately 25 nm). At other points the interface exerts a medium range repulsive force growing stepwise as the tip approaches the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 52 publications
7
54
0
Order By: Relevance
“…Experiments probing the interface between water and hydrophobic silicon have shown that the structure of water is perturbed ͑relative to the bulk liquid͒ 10-15 nm away from the interface. 13 It is in this region that we propose the ice embryos form. The growth of an ice embryo near the interface is hindered by the influence of the silicon; the spectra of both the thin films and droplets show water at the interface which is depleted in the icelike component relative to bulk water or ice at the same temperature, which is indicative of a liquidlike hydrogen bonding network.…”
Section: The Location Of the Critical Embryomentioning
confidence: 98%
“…Experiments probing the interface between water and hydrophobic silicon have shown that the structure of water is perturbed ͑relative to the bulk liquid͒ 10-15 nm away from the interface. 13 It is in this region that we propose the ice embryos form. The growth of an ice embryo near the interface is hindered by the influence of the silicon; the spectra of both the thin films and droplets show water at the interface which is depleted in the icelike component relative to bulk water or ice at the same temperature, which is indicative of a liquidlike hydrogen bonding network.…”
Section: The Location Of the Critical Embryomentioning
confidence: 98%
“…Moreover, the nearly unchanged form of the distribution lead us to believe that surface effects on the orientation will continue much further from the interface than we can probe in these simulations. These long-range effects on molecular orientation have recently been studied experimentally by Teschke and de Souza 29 in their atomic force microscopy ͑AFM͒ study of the gas-liquid interface. They show that AFM tips detect attractive forces at distances as far as 250 nm and attributed the phenomena to the broken hydrogen bonds at the interface.…”
Section: A Density and Molecular Orientationmentioning
confidence: 99%
“…Next, the cytoplasm was likened to a uniform medium with an electrical conductivity of s ¼ 0.22 S/m [Bai et al, 2006]. Regarding the appropriate value to be defined for its relative permittivity, it was set at an intermediate value of e r of 40, which is between the bulk state value of free water (e r-bulk % 80) and its bound state one (e r-bound % 2), usually considered very close to the cell wall [Teschke and De Souza, 2005]. The bacterium was considered immersed in a physiological medium (s ¼ 1.3 S/m, e r-bulk ¼ 80).…”
Section: Modelingmentioning
confidence: 99%